Peran Program Madrasah Haji Markaz Jam’iyyah Afaq al-Ma’rifah Arab Saudi dalam Meningkatkan Kualitas Ibadah Haji Jemaah Indonesia: The Role of the Madrasah Haji Program by Markaz Jam’iyyah Afaq Al-Ma’rifah, Saudi Arabia, in Enhancing the Quality of Hajj Performance Among Indonesian Pilgrims - Irsyad Rafi; Khaerul Aqbar; Azwar Azwar; Muhammad Ridwan (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
The Hajj Madrasah Program organized by Markaz Jam’iyyah Afaq Al-Ma’rifah, Saudi Arabia, represents an empowerment and accompaniment initiative for Indonesian Hajj pilgrims through integrated scholarly, spiritual, and practical religious guidance. This Community Service Program (Pengabdian kepada Masyarakat, PkM) aims to enhance the quality of Indonesian pilgrims’ Hajj performance by ensuring closer adherence to Islamic legal prescriptions through comprehensive understanding and continuous guidance. The program adopts a participatory approach implemented through religious short lectures (kultum), distribution of Hajj ritual guidebooks, and educational pilgrimages guided by qualified dā‘īs. The results indicate: (1) a significant improvement in pilgrims’ understanding of Hajj rituals as a result of intensive accompaniment and the use of structured guidebooks; (2) strengthened spiritual awareness through tazkiyat al-nafs activities and educational pilgrimages; and (3) increased pilgrim self-reliance facilitated by personalized consultations. The program’s contribution lies in its holistic approach—integrating education, spiritual development, and practical simulation—which offers an innovative model for Hajj guidance. Furthermore, the program serves as a training platform for dā‘īs, effectively bridging theoretical Islamic scholarship with applied religious practice.